Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1242/jcs.147033
|View full text |Cite
|
Sign up to set email alerts
|

Long QT mutations disrupt IKS regulation by PKA and PIP2 at the same KCNQ1 helix C-KCNE1 interface

Abstract: KCNQ1 and KCNE1 co-assembly generates the I KS K + current, which is crucial to the cardiac action potential repolarization. Mutations in their corresponding genes cause long QT syndrome (LQT) and atrial fibrillation. The A-kinase anchor protein, yotiao (also known as AKAP9), brings the I KS channel complex together with signaling proteins to achieve regulation upon b1-adrenergic stimulation. Recently, we have shown that KCNQ1 helix C interacts with the KCNE1 distal C-terminus. We postulated that this interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 53 publications
3
38
0
Order By: Relevance
“…Recent studies identified clusters of basic residues in the Kv7.1 membrane domain, specifically at the S2-S3 and S4-S5 intracellular linkers and in prehelix A, to be involved in PIP 2 binding (33,37,38). Another cluster of basic residues in helix C was also found to be involved in Kv7.1 current rundown after PIP 2 depletion (32,39). In addition, KCNE1 was found to increase PIP 2 sensitivity 100-fold over that of the Kv7.1 α-subunit alone (31).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies identified clusters of basic residues in the Kv7.1 membrane domain, specifically at the S2-S3 and S4-S5 intracellular linkers and in prehelix A, to be involved in PIP 2 binding (33,37,38). Another cluster of basic residues in helix C was also found to be involved in Kv7.1 current rundown after PIP 2 depletion (32,39). In addition, KCNE1 was found to increase PIP 2 sensitivity 100-fold over that of the Kv7.1 α-subunit alone (31).…”
Section: Significancementioning
confidence: 99%
“…Several clusters of basic residues have been identified in the Kv7.1 CT as potential PIP 2 binding sites, including sites in prehelix A and helix C (32,34,37,39). Therefore, we purified Histagged Kv7.1 CT that lacks helices C and D (352-539, Δ406-504) and checked whether the competition of Ca 2+ -CaM to PIP 2 binding still occurred in PIP 2 pulldown assays.…”
Section: +mentioning
confidence: 99%
“…Immediately after the last S6 transmembrane segment, the intracellular membrane proximal half (AB) is important for CaM binding and channel gating. Three-dimensional (3D) reconstitution locates the intracellular distal part (helix D) far from the membrane (Dvir et al, 2014b), which directs oligomerization and partner specificity (Yus-Nájera et al, 2002;Howard et al, 2007;Haitin and Attali, 2008). The AB and D helices are connected by helix C, indispensable for function, and a linker of variable length.…”
Section: Introductionmentioning
confidence: 99%
“…The AB and D helices are connected by helix C, indispensable for function, and a linker of variable length. Mutagenesis suggests that, in addition to the S4-S5 linker and the proximal C-terminus, helix C contributes to PIP 2 regulation (Dvir et al, 2014b;Zaydman and Cui, 2014). CaM binding is essential for Kv7 channels to exit from the endoplasmic reticulum, and influences heteromeric assembly of Kv7.2/3 channels and subsequent enrichment at the axonal initial segment (Yus-Nájera et al, 2002;Devaux et al, 2004;Chung et al, 2006;Etxeberria et al, 2008;Haitin and Attali, 2008;Alaimo et al, 2009;Cavaretta et al, 2014;Chung, 2014;Liu and Devaux, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…First, we analyzed the trafficking of these complexes to the plasma membrane, which, in some mutations, explains the decrease of the current [23,25,26]. Subcellular distribution of D242N KV7.1-KCNE1 resembled that of WT KV7.1-KCNE1 channels ( Figure 3A and 3B).…”
Section: Loss Of Function Of D242n Kv71-kcne1 Channelsmentioning
confidence: 99%